The Relationship Between the Shari'ah, Tariqah, Haqiqah and Ma'rifah by Wan Sulaiman b Wan Siddik , a 19th Malay Sufi Scholar in the Malay world. - Muhammad Khairi Mahyuddin; Zakaria Stapa; Faudzinaim Badaruddin (American Research Institute for policy development, 2024)
This paper utilizes a content study to clarify the concepts and relationship between sharicah, tariqah, haqiqah,and macrifah by Wan Sulaiman b. Wan Siddik, a Malay Sufi scholar in 19thin the Malay world. He clarifies these four terminologies in his epistle Mizan al-uqala’ wa al-udaba’ due to many misconceptions about this matter by his Sufi Malay local. The impact of misconceptions causessome Sufi local Malay to discount sharicah as outward skin by givingpreference to tariqah, haqiqah, and macrifah as these three are the kernel of sharicah. At the end, the study singles out that these four terminologies are one substance of the sharicah and no dichotomy to disconnect its teaching to each other and no contradictory and distinction from the sharicah as the holistic teaching. Thedifferencesonlyrelyupontoitsexpressions andterminologiesutilizedforthesakeofclarity.